Development and validation of the Taiwan Children's Health Literacy Test. (June 2018) - Liu, Chieh-Hsing; Liao, Li-Ling; Cheng, Chi-Chia J.; Chang, Tzu-Chau
Background: Currently, health literacy (HL) worldwide is measured primarily among adults from a medical perspective. A children's HL test from a health promotion perspective is needed. This study develops the Taiwan Children's Health Literacy Test (TCHL) targeted at Taiwanese sixth-graders. Methods: HL indicators were identified through interviews of sixth-grade teachers, primary caregivers, and sixth-graders. They were used to develop a 25-item online test, which was finalized after pretesting and administered to a stratified random sample of 671 students across 29 sixth-grade classes. Results: The response rate was 87.2% (585 participants). Cronbach's α was 0.60–0.78 for the HL subtests and 0.79 for the overall HL test. Correlation coefficients among subtests ranged from 0.49 to 0.87. The average proportion correct was 0.80 for overall HL. In item response theory analysis, the difficulty level ranged from −2.77 to −0.40, while the degree of discrimination was 0.44–2.65. Item information peaked when the ability value was approximately −1.8. Furthermore, HL scores had a significant positive correlation with health behaviors. Conclusions: Overall, the test was found to be reliable and valid, with a low level of difficulty for basic HL ability. The present results can be used as a reference by government health education units to investigate national HL in children.